Keadilan Prosedural Partisipatif dan Pengembangan Karir Untuk Meningkatkan Kinerja Karyawan - Rusyanti Rusyanti (Papanda Publisher, 2022)
Performance is the work achieved by a person in carrying out his duties or work both in quantity and quality, namely in accordance with responsibilities and is the result of work that has been achieved by someone with predetermined standards. This research was conducted at PT. Pancaragam Toyindo Majalengka, as for the purpose of this study is to determine the effect of participatory procedural justice variables and career development on employee performance. The research method used in this research is a survey method with a descriptive verification approach. The data obtained are primary data, namely data from respondents' responses which are distributed to respondents. The population of all employees as many as 200 people and a sample taken is 100 people. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression, coefficient determination and hypothesis testing, for partial test using t-test and model feasibility test. Based on the results of hypothesis testing, participatory procedural justice has a positive and significant effect on employee performance. Career development has a positive and significant effect on employee performance.